Effect of forest management on the physicochemical properties of the soil in Ixtlán de Juárez, Oaxaca, Mexico - Rodríguez-Rivera, Viviana; Zaragosa-López, Karina; Clark-Tapia, Ricardo; Ramírez Santiago, Rosario (Instituto de Ecología, A.C., 2023)
One of the biggest problems facing forest management is the degradation and conservation of soil quality. The objective of this work was to carry out an analysis of physical and chemical aspects of the soil in areas subject to forest management in Ixtlán de Juárez, Oaxaca, to provide recommendations for forestry management and soil conservation. Three clear-cut strips and three adjacent sites of alternate vegetation were selected, in addition to a natural recovery site subject to agriculture and forest management in the past. Each site was subdivided into three altitudes (high, medium, and low) at which the soil's physical and chemical properties were analyzed through variance analysis and multivariate (PCA-principal component analysis, MDS-multidimensional scaling analysis, and heatmap). A significant effect of the clear-cut treatment was found on some physical (density, compaction, and porosity) and chemical (carbon, pH, conductivity, nitrogen, and magnesium) properties compared to alternate vegetation. The multivariate analysis of the physicochemical properties (ACP, MDS, and heatmap) grouped and correlated the alternate vegetation and natural recovery sites with altitude and differentiated them from the clear-cut sites. The study also suggests a recovery of soil quality in a few decades, given the similarity between areas of alternate vegetation and natural treatment. It is recommended not to practice complementary scarification treatments of the soil. However, on the contrary, its activity promotes the retention of the organic horizon to increase the possibility of maintaining the soil's physicochemical properties.